The Major Determinants Of Foreign Exchange Reserve: The Promise And Perils Of Pakistan Economic Crises - Arif Ullah, Muhammad Asif Shahzad, Kashif Raza, Sumera Bari, Abdul Muqeet (Migration Letters, 2024)
The focus of this study is to examine the relationship between foreign exchange rate, external debt, export, inflations and foreign exchange reserve in the context of Pakistan economic crises. The data was taken over the period from 1999 to 2022. The comprehensive time series methodology was used such as fully modified ordinary least squares, dynamic ordinary least squares, canonical cointegrating regression and Johansen cointegration was used for this study analysis. All the models used for the analysis shows robust relationship between dependent variable and independent variables. The outcomes reveal an inverse relationship between the foreign exchange rate and foreign exchange reserves. Both the fully modified ordinary least squares and canonical cointegrating regression models propose a negative correlation between external debt and foreign exchange reserves. Conversely, the dynamic ordinary least squares model indicates a positive connection between external debt and foreign exchange reserves. Furthermore, the results demonstrate a positive association between a country exports and its foreign exchange reserves. The analysis also validates that an increase in domestic inflation is correlated with a reduction in foreign exchange reserves. The results of the Johansen cointegration shows two vectors at 5% significant level cointegration between foreign exchange reserve and rest of the independent variables. [1]The distinctions revealed by different models underscore the complexity of these relationships, emphasizing the need for comprehensive policy measures. Finally, it is essential for the government to consistently oversee crucial indicators and be prepared to adjust policies in response to evolving circumstances. This may require periodic revaluation of exchange rate policies, debt management strategies, and export promotion initiatives in alignment with shifting economic conditions.